2020
DOI: 10.1515/biol-2020-0032
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the fecal microbiome of the Yangtze finless porpoise during a short-term therapeutic treatment

Abstract: AbstractThe fecal microbiome is an integral part of aquatic mammals, like an inner organ. But we know very little about this inner organ of the threatened aquatic species, Yangtze finless porpoise (YFP). Four YFPs were placed into a purse seine for skin ulceration treatment, and this opportunity was taken to nurse the animals closer. In particular, we collected the feces of the YFPs before and after the paired healing and therapeutic treatment, along with samples of their fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…The site-specificity of YFP bacteria inspired us to consider the influence of microbiota in studying the structural characteristics and physiology of various body sites of YFP. The intestinal bacteria of YFP was the first to attract the attention of researchers (McLaughlin et al, 2011(McLaughlin et al, , 2012(McLaughlin et al, , 2013Wan et al, 2016b;You et al, 2020). We identified some dominant genera not characterized in previous studies, including Romboutsia, Candidatus Arthromitus, Plesiomonas, and Actinobacillus.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The site-specificity of YFP bacteria inspired us to consider the influence of microbiota in studying the structural characteristics and physiology of various body sites of YFP. The intestinal bacteria of YFP was the first to attract the attention of researchers (McLaughlin et al, 2011(McLaughlin et al, , 2012(McLaughlin et al, , 2013Wan et al, 2016b;You et al, 2020). We identified some dominant genera not characterized in previous studies, including Romboutsia, Candidatus Arthromitus, Plesiomonas, and Actinobacillus.…”
Section: Discussionmentioning
confidence: 64%
“…YFP occupies the top ecological niche of the Yangtze River ecosystem, is carnivorous, and is a unique species for studying freshwater mammals ( Huang et al, 2017 ; Zhou et al, 2018 ). Currently, the studies related to the bacteria of YFP mainly focus on the fecal bacteria, mainly in the capture and semi-natural environments ( McLaughlin et al, 2011 , 2012 , 2013 ; Wan et al, 2016b ; You et al, 2020 ). In addition, Aeromonas veronii associated with the YFP disease has also been reported ( Liu et al, 2018 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The difference in microbiome composition may be individual- or species-specific. As reported in a previous study, the difference in health status or human care may contribute to the difference in the gut microbiome of cetaceans [ 4 , 43 ]. Moreover, common minke whales belong to the Balaenopteridae family, while both the Indo-Pacific finless porpoise and the narrow-ridged finless porpoise belong to the Phocoenidae family [ 30 ].…”
Section: Discussionmentioning
confidence: 96%
“…ceti is a common bacterial component with a high relative abundance in the intestinal microbial community of various dolphin species, including the striped dolphin ( Stenella coeruleoalba ) [28], common bottlenose dolphin [16, 29, 30], Indo-Pacific humpback dolphin ( Sousa chinensis ) [13], short-finned pilot whale ( Globicephala macrorhynchus ) [17], and Yangtze finless porpoise ( Neophocaena asiaeorientalis ssp. asiaeorientalis ) [12]. Our previous study on faecal samples of the common bottlenose dolphin and Indo‐Pacific bottlenose dolphin ( Tursiops aduncus ) revealed that almost all bacterial 16S rRNA V3-V4 region sequences assigned to Cetobacterium were identified to be C.…”
Section: Introductionmentioning
confidence: 99%
“…Several culturable aerobic and anaerobic bacteria [9,10] and primary bacterial pathogens [11] have been isolated from the common bottlenose dolphin (Tursiops truncatus). More recently, culture-independent approaches using next-generation sequencing technologies have provided more detailed information about the cetacean intestinal microbial community [12][13][14][15][16][17]. Despite increasing interest in the comprehensive intestinal microbiota of cetaceans, few studies have investigated the characteristics of each bacterial species in the cetacean intestine.…”
Section: Introductionmentioning
confidence: 99%